Autosomal dominant asymmetrical radial dysplasia, dysmorphic facies, and conductive hearing loss (facioauriculoradial dysplasia). Issue 2 (April 1982) - Harding, A E; Hall, C M; Baraitser, M
Abstract : A syndrome characterised by asymmetrical radial dysplasia, dysmorphic facies, conductive deafness, and external ear deformity is described in a mother and her daughter. This combination of anomalies has previously been reported in members of a single family. The disorder appears to be clinically and genetically distinct from others associated with radial dysplasia, such as Nager's acrofacial dysostosis and the lachrimoauriculoradiodental syndrome. Inheritance is autosomal dominant, with marked variation in expression of the mutant gene.